Implementation of the FCFS (First Come, First Served) Method to Resolve Customer Queuing Issues at Lentera Grill Restaurant: (Case Study: Web-Based Reservation Information System at Lentera Grill Restaurant) - Prabandaru, Lila; Suharyadi, Suharyadi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Lentera Grill Restaurant faces long customer queues due to manual ordering processes, particularly during peak hours. Our research aimed to reduce wait times and improve service accuracy through technology. We designed and built a web-based reservation system using Python, React, and MongoDB that applies the FCFS (First Come First Served) method to process orders in sequence of arrival. Testing involved two phases: functional validation through Blackbox Testing of all user pathways, and performance assessment using JMeter with 20, 50, and 100 simultaneous users. Results showed the system maintained stable throughput with zero error rates across all load scenarios, though we observed latency spikes during heavy traffic that require attention. The FCFS implementation reduced average wait times by 37% compared to the previous manual system and increased customer satisfaction ratings in post-implementation surveys. Restaurants with similar queue management challenges would benefit from adopting such technology-based solutions that balance customer experience with operational efficiency